Pengembangan Media Pembelajaran Berbasis KineMaster pada Materi Volume Bangun Ruang Menggunakan Kubus Satuan di Sekolah Dasar - Yuliana, Elsa; Ariani, Yetti (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2023)
Along with the development of technology, innovation in education should also increase. One of them is the use of the KineMaster video editor application in making learning media so that such media which is able to make students active in the learning process is created. The type of research used in this research is research and development with the ADDIE development model. ADDIE development model has some stages, namely Analysis, Design, Development, Implementation, and Evaluation. The subjects of the experiment in this study were 16 students in the fifth grade of SDN 12 Koto Baru. The research was conducted on Monday 27th and Tuesday 28th of March 2023. The results of this study obtained that the average result of the validation is 95.55% with the category very valid. The results of the teachers’ response questionnaires obtained 93,33% with category very practical, while the students response questionnaires at SDN 12 Koto Baru is 94,37% with category very practical. Thus, it can be concluded that this KineMaster-based learning media is qualified to be used in the learning process.